2022
DOI: 10.21203/rs.3.rs-1818132/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Earthquake and Rainfall Induced Landslide Hazard Assessment of Kutupalong Rohingya Camp Using Meteorological and Geological Information

Abstract: The study aims to assess the landslide hazard scenario of the Kutupalong Rohingya camp, considered one of the largest humanitarian shelters for conflict-fled people. The camp area lying in a prominent tectonic setting and meteorological environment, is vulnerable to landslide hazards, specifically in the monsoon season. The worst-case scenario of earthquake and rainfall occurrence at the same time or one after another is considered in this study. Landslide favorable parameters (topographic, soil physical prope… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Das et al ( 2023) [8] demonstrated that experts conducted landslide susceptibility zonation (LSZ) assessment for several regions of this seismically active high mountainous terrain utilizing a variety of methodologies, mostly spanning from conventional subjective views to sophisticated machine learning models. [30] all perform additional study on LSZ . The map combination strategy and the AHP method were consistently used with various area and mapping unit sizes, it has been observed.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al ( 2023) [8] demonstrated that experts conducted landslide susceptibility zonation (LSZ) assessment for several regions of this seismically active high mountainous terrain utilizing a variety of methodologies, mostly spanning from conventional subjective views to sophisticated machine learning models. [30] all perform additional study on LSZ . The map combination strategy and the AHP method were consistently used with various area and mapping unit sizes, it has been observed.…”
Section: Related Workmentioning
confidence: 99%
“…According to the investigations, the more points that lie along the x=y (red line), the more accurate the model is (in Figure [29]). Figure [30] displays the error function profile (Predicted value vs Actual value) for ANN-3. This graph is useful in determining the profile of the error function.…”
Section: Evaluation Of Ann-1mentioning
confidence: 99%